Search for Varicella Zoster Virus DNA in Saliva of Healthy Individuals Aged 20 to 59 Years - Birlea, Marius (2013)
All neurological and ocular complications of varicella zoster virus (VZV) reactivation can occur without rash. Virological verification requires detection of VZV DNA or anti-VZV IgG antibody in cerebrospinal fluid (CSF), or anti-VZV IgM antibody in serum or CSF. If VZV were readily detected in other tissue in patients with neurological disease without rash and found to correlate with tests listed above, more invasive tests such as lumbar puncture might be obviated. Saliva is a potential source of VZV DNA. To study the potential diagnostic value of detecting VZV DNA in saliva from patients with neurological disease, saliva of healthy adults searched for VZV DNA. A single saliva sample obtained by passive drool was centrifuged at 16,000 × g for 20 mins. DNA was extracted from the supernatant and cell pellet and examined in triplicate for VZV DNA by real time PCR. A single random saliva sample from 80 healthy men and women aged 20–59 years revealed no VZV DNA (Table 1), but was uniformly positive for cell (GAPdH) DNA. Because VZV DNA was not found in a random saliva sample from 80 individuals 20–59 years-old, a VZV-positive sample during neurologic disease may have potential significance. Further studies will determine whether VZV DNA in saliva correlates with VZV DNA or anti-VZV antibody in CSF in patients with neurological disease.